Harmony of Sacred Numbers Functions in the Works of Belles-Lettres from Islamic Perspective - Abduova, Nazilya; Abduov, Mukhammadgali; Kagazbayev, Zhanbyrbay; Sateeva, Botagoz; Kadina, Zhanby (Journal of Al-Tamaddun, 2023)
Since ancient times, numbers have played an important and multifaceted role in human life. In many cultures, especially in the Islamic one, individual numbers were given special significance. In this regard it is necessary to study the origin of so-called sacred numbers, which have been an important aspect of Islamic cultural heritage. The present research paper focuses on the semantics and meaning of "three", "seven" and "forty" which have become sacred numbers due to objective and subjective factors. An analysis of the use of a group of sacred numbers in Islam was researched. Also, the meaning of sacred numbers in everyday life was investigated. As a result of the comprehensive study, we can admit that special properties of sacred numbers lies in the law of creation. Special attention was paid to show the role of sacred numbers in revealing the artistic merits of works of fiction, as well as the peculiarities of their use in religious heritage. It is obvious that the main scientific conclusions drawn by the authors will be a renewed impetus, particularly for young researchers to develop new ideas in this field.